2006
DOI: 10.2310/7750.2006.00052
|View full text |Cite
|
Sign up to set email alerts
|

Are Narrow-Band Ultraviolet B Home Units a Viable Option for Continuous or Maintenance Therapy of Photoresponsive Diseases?

Abstract: Narrow-band ultraviolet B home phototherapy was found to be an effective form of maintenance therapy for photoresponsive diseases. It is safe and presents few side effects when patients receive appropriate guidelines, teaching, and follow-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…[1] The effectiveness of home phototherapy appears to be similar to that of hospital-based phototherapy and it appears to be safe and cost-effective. [2][3][4] To our knowledge, this is the first report of home phototherapy for vitiligo from China. In our study, most patients had good compliance.…”
Section: Narrow-band Ultraviolet B Home Phototherapy In Vitiligomentioning
confidence: 87%
“…[1] The effectiveness of home phototherapy appears to be similar to that of hospital-based phototherapy and it appears to be safe and cost-effective. [2][3][4] To our knowledge, this is the first report of home phototherapy for vitiligo from China. In our study, most patients had good compliance.…”
Section: Narrow-band Ultraviolet B Home Phototherapy In Vitiligomentioning
confidence: 87%
“…Compliance, adherence and patient uptake of phototherapy as a treatment for psoriasis is also improved compared with conventional hospital‐based care . When patient training and supervision have been optimized, as for example in the Netherlands, studies have demonstrated no difference in the acute adverse events or total cumulative UV dose between outpatient‐based and home‐based phototherapy, suggesting that the safety profile of both are similar …”
Section: Methodsmentioning
confidence: 99%
“…Location, work, and financial restrictions add to the difficulty for patients to maintain an adequate treatment schedule. 24 Surveys report that 40% 25 and 42% 26 of patients found hospital phototherapy inconvenient and 75% 26 of patients thought that home phototherapy would be helpful. The majority of nonexcimer units have been designed to be used privately in the home setting (Table I).…”
Section: Localized Uvb Phototherapymentioning
confidence: 97%